Characterization of novel small RNAs (sRNAs) contributing to the desiccation response of Salmonella enterica serovar Typhimurium - Barnhill, Emmaline C. (RNA Biol, 2019)
Noncoding RNA (ncRNA) modulation of gene expression has now been ubiquitously observed across all domains of life. An increasingly apparent role of ncRNAs is to coordinate changes in gene expressions in response to environmental stress. Salmonella enterica, a common food-born pathogen, is known for its striking ability to survive, adapt, and thrive in various unfavourable environments which makes it a particularly difficult pathogen to eliminate as well as an interesting model in which to study ncRNA contributions to cellular stress response. Mounting evidence now suggests that small RNAs (sRNAs) represent key regulators of Salmonella stress adaptation. Approximately 50–500 nucleotides in length, sRNAs regulate gene expression through complementary base pairing with molecular targets and have recently been suggested to outnumber protein-coding genes in bacteria. In this work, we employ small RNA transcriptome sequencing to characterize changes in the sRNA profiles of Salmonella in response to desiccation. In all, we identify 102 previously annotated sRNAs significantly differentially expressed during desiccation; and excitingly, 71 novel sRNAs likewise differentially expressed. Small transcript northern blotting and qRT-PCRs confirm the identities and expressions of several of our novel sRNAs, and computational analyses indicate the majority are highly conserved and structurally related to characterized sRNAs. Predicted sRNA targets include several proteins necessary for desiccation survival and this, in part, suggests a role for desiccation-regulated sRNAs in this stress response. Furthermore, we find individual knock-outs of two of the novel sRNAs identified herein, either sRNA1320429 or sRNA3981754, significantly impairs the ability of Salmonella to survive desiccation, confirming their involvements (and suggesting the potential involvements of other sRNAs we identify in this work) in the Salmonella response to desiccation.